(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Chronic renal disease is a common health problem in the world. In 2016, females are mostly affected by CKD than the males. There are many diagnostic methods in modern aspect of medicine like serum Creatinine, urea and etc., The Siddha system of medicine is a treasure dedicates to the world by Siddhars. In Siddha system of medicine, different diagnostic methods present for all diseases. As per Theraiyar, the eight methods of diagnosis ‘Envagaithervu’ are Naadi (pulse), Naa (Tongue), Niram (Color), Mozhi (Voice), Vizhi (Eyes), Malam (Feces), Neer (urine) and Sparisam (Touch). Among the eight diagnostic tools, Neikkuri is one of the important methods for urine analysis. This study was aimed to Observed the Neikkuri (oil on urine sign) in chronic kidney disease patients. 40 patients were selected from NIS OPD by non randomised method. The study details were collected in the data collection form with the consent of the patients. Urine samples were collected in glass bowel. A small drop of black sesame oil was instilled on the center of the upper surface of the urine perpendicularly. The spreading nature of the oil has to be observed. Result of the study shows 30% of Neikkuri is Kabapitham nature. This study is helps to evaluate the siddha diagnostic method for Chronic Kidney Disease.